2018
DOI: 10.1186/s13058-018-1060-5
|View full text |Cite
|
Sign up to set email alerts
|

Sortilin inhibition limits secretion-induced progranulin-dependent breast cancer progression and cancer stem cell expansion

Abstract: BackgroundCancer progression is influenced by genetic aberrations in the cancer cell population as well as by other factors including the microenvironment present within a tumour. Direct interactions between various cell types as well as cellular signalling via secreted cytokines can drive key tumourigenic properties associated with disease progression and treatment resistance. Also, cancer stem cell functions are influenced by the microenvironment. This challenging subset of cells has been linked to malignant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 49 publications
3
52
0
Order By: Relevance
“…Previous reports have associated high progranulin expression with ERα negative patients (16) as well as a predictive marker for recurrence in ERα positive breast cancer (29). We recently showed that progranulin secretion increased in ERα positive breast cancer when cells were subjected to hypoxia, whereas ERα negative breast cancer cells had constitutive high secretion of progranulin (7). Here we observed a signi cant link between progranulin and HIF1α, where tumors with high expression of HIF1α tend to express high progranulin.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Previous reports have associated high progranulin expression with ERα negative patients (16) as well as a predictive marker for recurrence in ERα positive breast cancer (29). We recently showed that progranulin secretion increased in ERα positive breast cancer when cells were subjected to hypoxia, whereas ERα negative breast cancer cells had constitutive high secretion of progranulin (7). Here we observed a signi cant link between progranulin and HIF1α, where tumors with high expression of HIF1α tend to express high progranulin.…”
Section: Discussionsupporting
confidence: 66%
“…Further, the progranulin receptor sortilin has been linked to breast cancer aggressiveness as well as being expressed in other types of cancer, such as prostate and ovarian cancer (31,36,37). Recent studies from our group have emphasized the stem cell propagating effect by progranulin through its receptor sortilin (7), indicating that this pathway could be central in mediating CSC properties during tumor progression. The existence of a targetable receptor further suggest that future cancer therapies could be developed, selectively targeting CSC propagation via sortilin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…86,87 Progranulin has been identified as a secreted CSC modulator that contributes to breast cancer progression. 88 Progranulin's role in tumor growth and therapy-induced resistance in various cancer types is associated with its binding to the neuronal receptor sortilin. [89][90][91] Interest on the downmodulation of sortilin in breast cancer treatment is increasing as it is associated with breast cancer metastatic potential.…”
Section: Substrate-selective Inhibitors Of Translocationmentioning
confidence: 99%